2023
DOI: 10.3390/su15065431
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Hybrid Ensemble Model Achieving Precision Education for Online Education Amid the Lockdown Period of COVID-19 Pandemic in Pakistan

Abstract: Institutions of higher learning have made persistent efforts to provide students with a high-quality education. Educational data mining (EDM) enables academic institutions to gain insight into student data in order to extract information for making predictions. COVID-19 represents the most catastrophic pandemic in human history. As a result of the global pandemic, all educational systems were shifted to online learning (OL). Due to issues with accessing the internet, disinterest, and a lack of available tools,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…They found that these methods can effectively determine best practices to predict students performance. 59 developed a generalizable hybrid machine learning model to identify attributes that regulate students performance prediction during the COVID-19 and achieved an overall accuracy of 98.6%. They compared their model with several other frequently used machine learning algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that these methods can effectively determine best practices to predict students performance. 59 developed a generalizable hybrid machine learning model to identify attributes that regulate students performance prediction during the COVID-19 and achieved an overall accuracy of 98.6%. They compared their model with several other frequently used machine learning algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…People began to devote themselves to mining some potential information from these massive data, which led to a variety of data mining technologies (Asad et al, 2023). Among them, education data mining is a new technology born in order to make full use of the huge data stream in the operation process of digital campus (Xu et al, 2023).…”
Section: Improving English Education Ability From the Perspective Of ...mentioning
confidence: 99%
“…Baker (2010) provided an overview of EDM, encompassing five research directions: relationship identification, model discovery, data distillation for human judgment, clustering analysis, and prediction modeling [11]. Among the five directions of EDM, prediction (evaluation) of academic performance is the most popular application [12][13][14][15]. Thai-nghe et al (2010) proposed an innovative recommendation system that evaluates students' academic performance by extracting education-related data [16].…”
Section: Introductionmentioning
confidence: 99%